2018
DOI: 10.1038/s41598-018-21549-w
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Bacterial Fitness with an Expanded Genetic Code

Abstract: Since the fixation of the genetic code, evolution has largely been confined to 20 proteinogenic amino acids. The development of orthogonal translation systems that allow for the codon-specific incorporation of noncanonical amino acids may provide a means to expand the code, but these translation systems cannot be simply superimposed on cells that have spent billions of years optimizing their genomes with the canonical code. We have therefore carried out directed evolution experiments with an orthogonal transla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Notably, in an effort to mimic the localization observed for Ru1 by adding 3nY onto agar plates (10 μL from a 20-mM stock solution), we observed a distinct halo pattern at the location at which 3nY was provided (Figure H and Figure S4). This marked difference with respect to supplying Ru1 is consistent with the previously observed toxicity of this ncAA at high concentrations . Thus, these results highlight the advantage of producing 3nY over time by a biocompatible catalyst, which does not show any apparent toxicity when applied onto agar plates containing live E. coli.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Notably, in an effort to mimic the localization observed for Ru1 by adding 3nY onto agar plates (10 μL from a 20-mM stock solution), we observed a distinct halo pattern at the location at which 3nY was provided (Figure H and Figure S4). This marked difference with respect to supplying Ru1 is consistent with the previously observed toxicity of this ncAA at high concentrations . Thus, these results highlight the advantage of producing 3nY over time by a biocompatible catalyst, which does not show any apparent toxicity when applied onto agar plates containing live E. coli.…”
supporting
confidence: 88%
“…This marked difference with respect to supplying Ru1 is consistent with the previously observed toxicity of this ncAA at high concentrations. 31 Thus, these results highlight the advantage of producing 3nY over time by a biocompatible catalyst, which does not show any apparent toxicity when applied onto agar plates containing live E. coli.…”
mentioning
confidence: 64%
“…Many microbes that colonise the human body can synthesise all 20 proteinogenic amino acids of humans, 95 , 96 and viruses can harness the host cell translational machinery to exclusively use the endogenous amino acid repertoire. It is believed that the human gastrointestinal tract harbours approximately 10 14 microbes, which, together, equate to roughly 1000 times the number of cells and 10000 times the DNA content of the human body.…”
Section: Tumour Neoantigens and Tumour Neoantigen Mimicrymentioning
confidence: 99%
“…By engineering the suppressor tRNA Tyr with two substitutions in the anticodon loop (G34C/G37A), Rauch et al further improved nTyr-incorporation efficiency [ 131 ]. Recently, Tack et al utilized an engineered β-lactamase that is structurally dependent on nTyr-incorporation to study the evolving fitness of bacteria with an expanded genetic code and they found that after 2000 generations of directed evolution, the fitness deficit of cells related to nTyr toxicity was overcome by adaptive mutations [ 132 ]. The most commonly mutated or deleted genes were amino acid transporters in the hydroxyl and aromatic amino acid permease family such as the tyrosine-specific permease TyrP and the tryptophan permease Mtr.…”
Section: Tyrosine Nitration By Genetic Code Expansionmentioning
confidence: 99%